Hybrid governance, violence, and peace agreement: An analysis of the north triple border area: Colombia, Brazil, and Peru - Nossa, Irene Cabrera; Pimenta, Marilia Souza [UNESP]; Suarez, Marcial A. Garcia (Univ Externado Colombia, Dept Publicaciones, 2024)
The article aims to discuss hybrid governance as part of a long-term peace project that began in 2016 and reaches the project of the government of Gustavo Petro, signed in the form of a law, based on the idea of a pact, or truce, which starts from a specific arrangement called Paz Total. Colombia's border with Peru and Brazil is examined in order to understand the distribution and disputes of the Carolina-Ramirez Front, the First-Front, and the Border- Commandos (BC). Through a review of these groups' interests and repertoires of violence, it is possible to distinguish three key clusters in the persistence of the armed conflict where these groups create social orders rivaling the peace objective of the current government. We propose to question how violence is regulated in these municipalities as a result of the established pact and the forms of hybrid governance, the latter understood as the juxtaposition of typical formal state governance, and local governance of a nonstate nature. Following this objective, this research combines a geo-referencing of the presence of dissident groups in the Amazonian border and their violence through Arcgis (Arc Geo-informatic System) software, the findings are supported by a review of secondary sources such as early warnings from the Ombudsman's Office and press reviews. We intend to highlight the importance of understanding these two dimensions of violence regulation: a) in regions where there is a juxtaposition between the presence of ex-combatants and a hybrid governance mode practiced by non-state actors, and; b) the importance of the contextual dimension to discuss the invisible pacts that allow a certain mode of governance and possible peace.
Keywords: Total peace; hybrid governance; borders; violence; Colombia.